(untitled) (Boston, 1996)
This unique reference provides the necessary information needed by both preservice as well as inservice educators to better understand and study the field of literacy education. Each of eleven chapters is based on a critical issue in the field of literary education, with topics such as whole language, literacy assessment, phonics, emergent literacy, and technology.
Keywords: Language arts,Reading,Nghệ thuật ngôn ngữ,Đọc hiểu